Determination of the electrochemical dissolution feasibility of a superalloy used in turbine components in alkaline solutions with additives - Kotok, Valerii; Sknar, Yuri; Butyrina, Tetyana; Sknar, Irina; Demchyshyna, Oksana; Chasova, Ella (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study was an electrochemical anodic dissolution of a heat-resistant nickel-based superalloy (≈62 wt.%), recovered from destroyed components of special-purpose equipment, which contains valuable metals such as Re (≈4 wt.%), Co, W, Mo, Ta, Nb, and others. The research addressed the problem of the lack of an effective electrochemical method for selectively extracting these components, particularly rhenium and other valuable elements, from such an alloy in alkaline media. The anodic behavior of the alloy was experimentally studied in 0.5 M NaOH in the presence of various complexing and activating additives (NaCl, citric acid, EDTA salt, and Na2H2P2O7). It was shown that none of the additives provided a significant acceleration of anodic dissolution. This was demonstrated by the fact that the increase in the average specific charge calculated for five cyclic voltammetry scans that contributed to alloy dissolution did not exceed 8%. In other cases, the values were significantly lower than in the base solution containing only alkali. It was established that the anodic dissolution process has a surface-selective nature: Ni, Co, Cr, Re, and Al are leached into the electrolyte, while a residual surface layer enriched in W, Ta, Nb, and Mo forms, hindering further dissolution. X-ray fluorescence analysis data confirmed changes in the chemical composition (Ni content decreased to ≈48 wt.%, W increased from ≈9 to ≈20 wt.% on the surface). Theoretical justification of the results is provided, based on the physicochemical properties of compounds that may form during anodic dissolution in the presence of additives. The absence of an activating effect from the additives suggests the need for further studies on pure NaOH. The obtained data are of practical importance for the selective separation of superalloy elements before further processing